APLIKASI KARBON AKTIF DARI CANGKANG KELAPA SAWIT SEBAGAI ADSORBEN PADA MINYAK JELANTAH BAHAN B SABUN - Pada Mulia Raja; Giyanto (Jurnal Agro Fabrica, 2020)
Used cooking oil is oil left over from frying that can no longer be used for frying because it has decreasednutritional value and has a negative impact on health. Used cooking oil can still be used as an example as araw material for making soap after being treated with used cooking oil. This study aims to make soap fromused cooking oil as raw material after being adsorbed using activated carbon from oil palm shells. The stagesof this research are 1). Making activated carbon from oil palm shells, 2). Applying activated carbon frompalm oil shells to used cooking oil, 3). Making soap from used cooking oil that has been adsorbed withactivated carbon from oil palm shells and 4). Testing the quality of soap, namely moisture content, soapingnumber and foam quantity. The results showed that the characteristics of the soap produced with an averagewater content of 7.5% (SNI 196-206 Max 15%), Sapling Number 196.90 mg / gr (SNI 196-206 mg/gr) and theamount of foam 1, 58 ml. Soap made from used cooking oil as raw material that has been adsorbed usingactivated carbon from oil palm shells in accordance with SNI 196-206 mg/gr.